Resepsi Surat Al-Kahfi Pada Hari Jumat Dalam Perspektif Living Qur'an: Analisis Kepustakaan Terhadap Hadis Keutamaan Dan Praktik Keagamaan Muslim - Syamsudin, Enep; Suryaman; Muslim (Dirosah Islamiyah, 2026)
The tradition of reading Surah Al-Kahf on Friday represents a widespread Living Qur'an phenomenon across diverse Muslim communities in Indonesia. This library research aims to analyze the normative foundations of the authentic hadiths regarding the virtues of Surah Al-Kahf and systematically map the varying typologies of reception using Hans Robert Jauss’s reception theory, Karl Mannheim's sociology of knowledge, and Alfred Schutz's phenomenological approach. By synthesizing findings from 25 empirical fields, including boarding schools (pesantren), urban assemblies, corporations, and social media promotions, this study demonstrates that while the practices are strongly anchored in the classical texts of Ahlus Sunnah wal Jama'ah—promising spiritual illumination (an-nūr) and protection against the eschatological tribulations of Dajjal—their operationalized reception splits into exegesis, symbolic, and dynamic functional domains. The synthesis reveals that the community's *horizon of expectation* converts the four core narratives of Surah Al-Kahf (faith, wealth, knowledge, and power) into transformative socio-spiritual mechanisms. These mechanisms facilitate internal coping instruments against contemporary societal challenges, shifting the communal reading from forced institutional compliance to autonomous, identity-driven protection and psychological tranquility